2012
DOI: 10.1159/000333103
|View full text |Cite
|
Sign up to set email alerts
|

Expression of SOCS1 and SOCS3 Is Altered in the Nasal Mucosa of Patients with Mild and Moderate/Severe Persistent Allergic Rhinitis

Abstract: Background: The aim of this study was to evaluate the role of suppressor of cytokine signaling (SOCS) molecules, SOCS1 and SOCS3, which act as negative regulators of cytokine signaling in various allergic diseases, in patients with mild and moderate/severe persistent allergic rhinitis. Methods: The expression and distribution pattern of SOCS1 and SOCS3 were analyzed in nasal mucosa and peripheral blood mononuclear cells (PBMC) of healthy controls, and patients with mild and moderate/severe persistent allergic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 50 publications
2
11
0
Order By: Relevance
“…It blocks the phosphorylation of STAT6 through inhibiting JAK activity, and has been identified as a negative feedback regulator of the JAK/STAT6 pathway . Mucosal SOCS1 is increased in patients with AR and asthma compared with healthy controls . The present study results proved consistent with published data showing that IL‐13 or IL‐17A stimulation upregulated SOCS1 expression in airway epithelial cells .…”
Section: Discussionsupporting
confidence: 92%
“…It blocks the phosphorylation of STAT6 through inhibiting JAK activity, and has been identified as a negative feedback regulator of the JAK/STAT6 pathway . Mucosal SOCS1 is increased in patients with AR and asthma compared with healthy controls . The present study results proved consistent with published data showing that IL‐13 or IL‐17A stimulation upregulated SOCS1 expression in airway epithelial cells .…”
Section: Discussionsupporting
confidence: 92%
“…SOCS1 and SOCS3 mRNA and protein expression was significantly increased in the nasal mucosa and PBMCs of patients with mild and moderate/severe persistent AR compared with healthy controls [36]. In our study, SOCS1 and SOCS3 mRNA were also highly expressed in the nasal mucosa and PBMCs in AR patients.…”
Section: Discussionsupporting
confidence: 63%
“…24 Interleukin-13 also plays a vital role in the regulation of allergic illness pathogenesis via amplification of immediate hypersensitivity. 8,11 Interleukin-5 is responsible for infiltration of eosinophilia in the airway, which leads to late-phase allergic response. 22,25 Furthermore, clinically, it has been documented that patients with AR are associated with elevated levels of IL-17 in nasal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggested that balance between Th1 cells and Th2 cells plays a vital role in the maintenance of the immune health, and its dysregulation leads to the induction of allergic responses. 8,9…”
Section: Introductionmentioning
confidence: 99%